Hydrodynamics of the Indus Valley Civilization: Ingenious Water Management through Physics - Pharswan, Jaibir Singh; Badoni, Badrish (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
One of the earliest of such urban cultures (circa 3300 and 1300 BCE), the Indus Valley Civilization (IVC) displayed an advanced level of water management and incorporated simple principles of physics when designing its hydraulic systems. This paper examines how the IVC’s engineers applied concepts of fluid mechanics, gravity, and the pressure differential to create an efficient, sustainable irrigation network. At Mohenjo-Daro, Harappa, and Dholavira, excavations have uncovered sprawling motley of reservoirs, step-wells, underground drains, and public baths, built to maximize the flow and storage of water. “Da vinci code” to the new civilization's engineering choice depended on Bernoulli's equation and Pascal's law to control the water pressure in the closed drainage system of the new civilization where waste was disposed of on an hourly basis to avoid flood within a specific interval. Gentle slopes incorporated into drainage channels utilized gravitational potential energy to facilitate a continuous transport of wastewater, minimizing stagnancy and contamination. Additionally, well reservoirs were designed based on the principles of capillary action and hydraulic gradient to allow the extraction of water and control its seepage. The IVC also showcases an evolved concept of urban planning besides the incorporation of hydrodynamic principles in routing the combined monsoonal water through the harvesting systems to ensure water supply throughout the year. The precision of these structures points towards an experiential mastery of hydrostatics, enabling them to stockpile water without over seepage and overflow. The paper concludes that the water-management strategies of Indus Valley civilization were both technologically advanced and environmentally humane. Through intuitive application of fundamental physics principles, the IVC had struck a balance between urbanization and natural resource conservation—a feat that is still applicable to contemporary water management systems. Such ancient knowledge acts as a formidable source of knowledge to overcome modern-day hydrologic challenges and signifies the continued relevance of early scientific thinking in human society.